Poda Na Lima As a Learning Model For Independent Learning Curriculum - Silvi Tabah Hati (Edumaspul: Jurnal Pendidikan, 2023)
Abstract Poda Na Lima is the advice of elders who have gone down and down for the angkola-mandailing community This paper wants to see the philosophy of Poda Na Lima as a learning model for the independent learning curriculum. The study was conducted for six months. This research was conducted in Batang Baruhar Jae Village located in Gunung Tua-North Sumatra.This type of research is qualitative using a realist ethnographic approach. The Realist ethnographic approach is used by researchers to be able to draw the situation of Ethnic Values in the Angkola-Maindailing community objectively, without being influenced by other elements. Data collection techniques are carried out by observation, in-depth interviews and literature studies that examine directly about Poda Na Lima. Primary data are traditional elders and teachers of Tanjung Malipe State Elementary School (SDN). The results of the study concluded that the philosophy of Poda Na Lima consists of 1) Paias Rohamu (cleanse your heart), 2) Paias Pamatangmu (clean your body), 3) Paias Parabitonmu, (clean your clothes), 4) Paias Bagasmu (clean your house), and 5) Paias Pakaranganmu (clean your yard / environment). Meanwhile, in its implementation, the principle of Poda Na Lima as a learning model of the independent learning curriculum is seen in congregational dhuha prayers and reading the Quran which is done every day is the first aspect (Paias Rohamu). Emphasis on Discipline of Environmental Love, Examination of students who do not bathe from home by BP and Coaching Competition Participants and Talents Student achievement is an aspect of Paias Pamatangmu.Provision or procurement of school media is the third principle (Paias Paribotanmu). While the promulgation of characters and the giving of "ornamental believers" day is the fourth aspect (Paias Bagasmu). The last aspect (Paias Alamanmu) in the implementation is in the form of community service and service programs. Keywords: Poda Na Lima, Elementary School, Angkola-Mandailing, Curriculum Merdeka Belajar. Poda Na Lima Sebagai Model Pembelajaran Untuk Kurikulum Merdeka Belajar Abstrak Poda Na Lima adalah nasehat para sesepuh yang telah turun turun untuk masyarakat angkola-mandailing Tulisan ini ingin melihat filosofi Poda Na Lima sebagai model pembelajaran kurikulum merdeka belajar. Penelitian dilakukan selama enam bulan. Penelitian ini dilakukan di Desa Jae Batang Baruhar yang terletak di Gunung Tua-Sumatera Utara.Jenis penelitian ini bersifat kualitatif dengan menggunakan pendekatan etnografi realis. Pendekatan etnografi Realis digunakan oleh peneliti untuk dapat menggambarkan situasi Nilai Etnis dalam masyarakat Angkola-Maindailing secara objektif, tanpa dipengaruhi oleh unsur-unsur lain. Teknik pengumpulan data dilakukan dengan observasi, wawancara mendalam dan studi literatur yang meneliti langsung tentang Poda Na Lima. Data primer adalah tetua adat dan guru Sekolah Dasar Negeri (SDN) Tanjung Malipe. Hasil penelitian menyimpulkan bahwa filosofi Poda Na Lima terdiri dari 1) Paias Rohamu (membersihkan hati), 2) Paias Pamatangmu (membersihkan tubuh), 3) Paias Parabitonmu, (membersihkan pakaianmu), 4) Paias Bagasmu (membersihkan rumahmu), dan 5) Paias Pakaranganmu (membersihkan halaman/lingkunganmu). Sedangkan dalam pelaksanaannya, prinsip Poda Na Lima sebagai model pembelajaran kurikulum merdeka belajar dilihat pada shalat dhuha berjamaah dan membaca Al-Quran yang dilakukan setiap hari merupakan aspek pertama (Paias Rohamu). Penekanan pada Disiplin Cinta Lingkungan, Ujian siswa yang tidak mandi dari rumah oleh BP dan Coaching Competition Peserta dan Bakat Prestasi siswa merupakan aspek dari Paias Pamatangmu.Penyediaan atau pengadaan media sekolah adalah prinsip ketiga (Paias Paribotanmu). Sedangkan pengumuman tokoh dan pemberian hari "ornamental believers" adalah aspek keempat (Paias Bagasmu). Aspek terakhir (Paias Alamanmu) dalam pelaksanaannya adalah dalam bentuk program pengabdian dan pengabdian kepada masyarakat. Kata kunci: Poda Na Lima, SD, Angkola-Mandailing, Kurikulum Merdeka Belajar.